Influence of Carboxymethyl Cellulose on the Stability, Rheological Property, and in-vitro Digestion of Soy Protein Isolate (SPI)-Stabilized Rice Bran Oil Emulsion - Zhang, Wenguan; Hao, Jia; Yuan, Yanan; Xu, Duoxia (Frontiers in Nutrition, 2022)
In this study, carboxymethyl cellulose (CMC) was added to soybean protein isolate (SPI)-stabilized rice bran oil (RBO) emulsion to improve its physicochemical stability and free fatty acid (FFA) release characteristics. RBO emulsions stabilized by SPI and various contents of CMC were prepared and assessed by measuring zeta-potential, particle size, transmission and microstructure, the rheological properties were analyzed by dynamic shear rheometer. In addition, its chemical stability was characterized by a storage experiment, and the FFA release was explored by a simulated gastrointestinal tract (GIT) model. It showed that the negative charge of the droplets of RBO emulsion was increased with increasing CMC content. The decrease in transmission of SPI-stabilized RBO emulsion with increasing CMC content was due to the droplets not being free to move by the special network interaction and an increase in the viscosity. According to the determination of the reactive substances of lipid hydroperoxide and thiobarbituric acid during 30 d storage at 37 ℃, the chemical stability of the emulsion added with CMC was enhanced compared with the SPI-stabilized RBO emulsion. In vitro digestion studies not only evaluated the structural changes of RBO emulsions at different stages but also found that RBO emulsion with CMC showed a higher level of free fatty acids release in comparison with that without CMC. It indicated the utilization of CMC can improve the bioavailability of RBO emulsions.